Investigation of Improving Postural Control Kinetic Parameters in Martial Art Athletes after applying tDCS - Mehran Delfani; Mahtab Arabi (University of Tehran, 2019)
tDCS is a neuromodulatory technique that induces a low intensity direct current into brain cells that stimulates or inhibits spontaneous neural activity. In recent decades, electrical stimulation has been used as an effective method to improve balance in different individuals. The aim of this study was to investigate the improvement of postural control kinetic parameters in martial art athletes after applying tDCS. Participants were 20 male martial art athletes aged between 18 and 25. 10 subjects in the experimental group were exposed to electrical stimulation for 1-3 mA for 15-20 minutes and 10 subjects in the control group were exposed to sham tDCS. Then, both groups were evaluated by SOT postural control to exposed variables in sensory organizing test. Data were analyzed using covariance analysis test to differentiate the effect of training interventions on postural control of the two groups (P<0.05). The findings showed that tDCS had a significant effect on the postural control of male martial art athletes in 3 values of equilibrium: the exclusion of information in proprioceptive systems, the exclusion of information in proprioceptive and visual systems and the provision of incorrect visual inputs. Finally, this study showed that tDCS could improve and enhance postural control kinetic parameters in martial art athletes